Expression of KAI1 and tenascin, and microvessel density are closely correlated with liver metastasis of gastrointestinal adenocarcinoma. Issue 1 (12th May 2006) - Zheng, Huachuan; Tsuneyama, Koichi; Cheng, Chunmei; Takahashi, Hiroyuki; Cui, Zhengguo; Nomoto, Kazuhiro; Murai, Yoshihiro; Takano, Yasuo
Abstract : Aim: To seek good markers to predict invasion and metastasis of gastrointestinal adenocarcinoma (GIA). Methods: Expression of KAI1 and tenascin were examined on tissue microarrays containing gastric adenocarcinoma (n = 98), colorectal adenocarcinoma (n = 125), gastric adjacent non-cancerous mucosa (n = 95) and colorectal adjacent non-cancerous mucosa (n = 112) by immunostaining. Microvessel density (MVD) in GIA was labelled using anti-CD34 antibody by immunostaining. Expression of KAI1 and tenascin, and MVD were compared with clinicopathological features of tumours, including PTEN (phosphatase and tensin homology deleted from human chromosome 10) and EMMPRIN (extracellular matrix metalloproteinase inducer) expression. Results: KAI1 expression was higher in GIAs than in their adjacent non-cancerous mucosa (p<0.05). KAI1 and tenascin expression showed a significantly negative association with liver metastasis of GIA (p<0.05), but not with depth of invasion, venous invasion or lymph node metastasis (p>0.05). A significantly negative relationship was observed between EMMPRIN and tenascin expression in GIA (p<0.05). MVD was positively correlated with depth of invasion, venous invasion, lymph node metastasis and liver metastasis of tumours (p<0.05), whereas it was negatively correlated with PTEN expression (p<0.05). Conclusions: Up-regulated KAI1 expression may play an important part in malignant transformation of gastrointestinal epithelial cells. Reduced expression of KAI1 and tenascin might underlie the molecular basis of liver metastasis of GIA. Angiogenesis is a key event in the invasion and metastasis of GIA. These markers might be used to indicate liver metastasis of GIA in clinicopathological practice.